ФИЗИКА ДАРСЛАРИДА ТАДҚИҚОТЧИЛИК ҚОБИЛИЯТИНИ РИВОЖЛАНТИРУВЧИ ИЖОДИЙ ФИКРЛАШ КОМПОНЕНТИНИНГ ЎРНИ - Рахмонов, И.А. (SCIENCE and SOCIETY, 2023)
This article studies the issues of developing research skills among students were considered, and the component of creative thinking was singled out as a component that develops research skills. The analysis of questions is given corresponding to this component.